Intervensi gizi terhadap kejadian stunting pada balita usia 6-24 bulan - Janggu, Jayanthi Petronela; Hamat, Viviana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Stunting is still a national and global problem because of its impact on the quality of future generations. There are many factors that cause stunting, so it is necessary to analyze which factors are strong candidates for stunting in the village locus. Purpose: To analyze the effect of nutritional interventions on the incidence of stunting in children under five. Method: Quantitative research with cross-sectional design. Data collection was carried out using a structured questionnaire that had been tested and carried out anthropometric measurements. The research was conducted at the stunting village locus selected by purposive sampling, namely in Lentang Village, Manggarai Regency, East Nusa Tenggara Province. Conducted in December 2022-April 2023. The total sample was 87 toddlers obtained based on the locus data list. Results: Multivariate analysis showed that the age of the baby was related to the incidence of stunting (p=0.02) with an OR value of 3.366. Furthermore, the income variable is related to the incidence of stunting (p=0.03) with an OR value of 3.456. The variable early initiation of breastfeeding has a relationship with the incidence of stunting (p=0.015) with an OR value of 3.576. Apart from that, the variable providing additional food has a relationship with the incidence of stunting (p=0.04) with an OR value of 3.25. Conclusion: Nutritional interventions that are related and have strong candidates for influencing the incidence of stunting are the provision of additional food and the age of children under five. Apart from that, nutritional intervention. Early initiation of breastfeeding is the factor that has the most influence on the incidence of stunting. Suggestion: The government, health services and the community must work together to improve stunting reduction programs, especially for children under 2 years of age and mothers. Keywords: Nutrition Interventions; Stunting; Toddlers. Pendahuluan: Stunting masih menjadi masalah nasional dan global karena dampaknya terhadap kualitas generasi mendatang. Multi faktor penyebab terjadinya stunting, sehingga perlu dianalisis faktor apa saja yang menjadi kandidat kuat terjadinya stunting di desa lokus. Tujuan: Untuk menganalisis pengaruh intervensi gizi terhadap kejadian stunting pada balita. Metode: Penelitian kuantitatif dengan desain cross-sectional. Pengumpulan data dilakukan dengan menggunakan kuesioner terstruktur yang telah diuji dan dilakukan pengukuran antropometri. Penelitian dilakukan di desa lokus stunting yang dipilih secara purposive sampling yaitu di Desa lentang Kabupaten Manggarai Provinsi Nusa Tenggara Timur. Dilaksanakan pada bulan Desember 2022- April 2023. Jumlah sampel sebanyak 87 balita diperoleh berdasarkan daftar data lokus. Hasil : Analisis multivariat menunjukkan bahwa faktor usia bayi memiliki keterkaitan dengan kejadian stunting (p=0.02) dan OR sebesar 3.366. Selanjutnya variabel pendapatan memiliki keterkaitan (p=0.03) dan OR sebesar 3.456. Variabel IMD memiliki hubungan dengan kejadian stunting (p=0.015) dan OR sebesar 3.576. Selain itu, variabel PMT memiliki hubungan dengan kejadian stunting (p=0.04) dan OR sebesar 3.25. Simpulan: Intervensi gizi yang terkait dan memiliki kandidat kuat dalam memengaruhi kejadian stunting adalah pemberian makanan tambahan (PMT) dan usia balita. Selain itu, intervensi gizi inisiasi menyusui dini (IMD) menjadi faktor yang paling berpengaruh terhadap kejadian stunting. Saran: Pemerintah, pelayanan kesehatan, dan masyarakat harus bekerjasama dalam meningkatkan program penurunan stunting terutama berfokus pada anak di bawah usia 2 tahun dan ibu. Kata Kunci: Balita; Intervensi Gizi; Stunting.